The effect of face-to-face versus web-based structured peer review on writing improvement: Evidence from ESP students - Pourhosein Gilakjani, Abbas; Sheikhy Behdani, Reihaneh (LPMPP Universitas Negeri Yogyakarta, 2024)
Engaging students in peer review to improve their writing has become a pedagogical approach. However, little evidence has supported the effects of web-based (WB) peer evaluation on students' writing enhancement. In terms of linguistic features, the present study, employing a quasi-experimental design, investigated the effect of WB versus face-to-face (FTF) peer review on ESP students' writing. Three intact classes (N = 48, 53) were split into two experimental groups and one control group at random to achieve this aim. The results of the pretests revealed that all the participants were homogenous concerning language proficiency and writing ability based on the Oxford Quick Placement Test (OQPT) and a writing test. While there was no peer review for the control group, the two experimental groups practiced peer review, one through FTF interaction and one via Peermark, a WB program provided through Turnitin. The findings indicated that the experimental group outperformed the control group. The findings also showed that the FTF group outperformed the WB group in writing. However, the analysis of linguistic features in the two modes of peer review demonstrated that WB interaction can be more effective in improving writing fluency than FTF peer review. Implementation of the findings for teachers and teacher trainers has been discussed.